2003
DOI: 10.1177/003693300304800208
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Hydatid Cyst of the Breast

Abstract: Although common in sheep-breeding communities, hydatid disease is actually found worldwide. Man is an occasional intermediate host in whom the disease is manifested by the presence of one or more hydatid cysts, usually located in the liver or lung and rarely at other sites such as the breast, as in our patient. A case of an isolated breast involvement that was diagnosed during surgery is presented and is followed by a brief discussion on the topic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 5 publications
0
37
0
Order By: Relevance
“…It was reported that a majority of secondary cysts occurred due to the rupture of the cyst in the liver. The breast can be a primary site or part of a disseminated hydatidosis [4,5] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that a majority of secondary cysts occurred due to the rupture of the cyst in the liver. The breast can be a primary site or part of a disseminated hydatidosis [4,5] .…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative diagnosis can be made by fine needle aspiration cytology where scoleces, hooklets or laminated membrane can be identified. It is a safe procedure, as no complications were mentioned in the literature [5,12] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although fine-needle aspiration cytology in diagnosis of echinococcosis is documented as a safe procedure in literature, that can demonstrate scoleces, hooklets or laminated membrane [3,[10][11][12][13], but it is not commonly used in the suspected cases as has happened in the present case. If it had been employed in our patient, the residual ectocyst might have resolved after 1-2 ultrasound-guided percutaneous aspirations and the patient might have been saved off a major operation.…”
Section: Discussionmentioning
confidence: 99%
“…Liver is the most commonly affected organ (70%), followed by the lung (20%) and other organs such as brain, thyroid, spleen, pancreas, gallbladder, etc. (10%) [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%